Small Maar Lakes of Luzon Island, Philippines their limnological status and implications on the management of tropical lakes – a review - Mendoza, Milette U. (Philippine Journal of Science, 2019)
In developing countries such as the Philippines, the inadequacy of even the most basic limnological datasets available has hindered planning and implementation of science-based management policies for inland waters. This situation is aggravated by overutilization of natural resources for ecosystem services such as water usage, aquaculture, fishing, and tourism. We reviewed published researches related to the Seven Maar Lakes (SMLs) in Luzon Is., Philippines to summarize information invaluable for the protection and sustainable use of these resources. Popular scientific search engines were utilized to gather peer-reviewed research articles and reports from both private institutions and government agencies. Literature and timeline from the 1930s to 2019 was classified into topics – namely socioeconomics, fisheries, biodiversity, and environment. Based on the literature survey, a variety of challenges, knowledge gaps, and promising research directions were identified, which are essential to the sustainable ecosystem management of the SMLs. Aquaculture practices impacting the lakes and its underestimated biodiversity were described. Measured vertical profiles of dissolved oxygen (DO), temperature, conductivity, pH, and salinity was supplemented by our preliminary limnological survey in the SMLs. Past and present monitoring data of selected physicochemical parameters were assessed from which the changing limnological status of the lakes was determined. We recommended measures motivated by strategic environmental assessments while still considering maintained economic yields. A sustained collaborative effort from different sectors is strongly suggested not only to manage the SMLs but also to address trade-offs among critical ecosystem services. Aside from the need for well-designed, long-term water quality monitoring, we also stress the synergistic interpretation of all available knowledge, which can contribute to the resolution of environmental issues at both local and global scales.